2003
DOI: 10.1002/gepi.10223
|View full text |Cite
|
Sign up to set email alerts
|

Variants of developmental genes (TGFA, TGFB3, and MSX1) and their associations with orofacial clefts: A case‐parent triad analysis

Abstract: We selected 262 case-parent triads from a population-based study of orofacial clefts in Norway, and examined variants of developmental genes TGFA, TGFB3, and MSX1 in the etiology of orofacial clefts. One hundred seventy-four triads of cleft lip cases (CL+/-P) and 88 triads of cleft palate only cases (CPO) were analyzed. There was little evidence for an association of any of these genes with CL+/-P. The strongest association was a 1.7-fold risk with two copies of the TGFB3-CA variant (95% CI=0.9-3.0). Among CPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
4
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 35 publications
4
79
4
9
Order By: Relevance
“…8,11,19,20 In the present research, no transmission distortion was found in the transmission disequilibrium analysis for either MSX1-CA or TGFB3-CA intragenic markers, but TGFB3-CA exhibited a trend to excess maternal transmission. Our findings suggest that both the maternal and fetal RR results are in agreement for both TGFB3-CA alleles, as the 163-bp allele had a deleterious recessive effect, whereas the 165-bp allele had a protective recessive effect.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…8,11,19,20 In the present research, no transmission distortion was found in the transmission disequilibrium analysis for either MSX1-CA or TGFB3-CA intragenic markers, but TGFB3-CA exhibited a trend to excess maternal transmission. Our findings suggest that both the maternal and fetal RR results are in agreement for both TGFB3-CA alleles, as the 163-bp allele had a deleterious recessive effect, whereas the 165-bp allele had a protective recessive effect.…”
Section: Discussioncontrasting
confidence: 52%
“…3,4 Their involvement is further supported by linkage and association studies in populations of different ethnic origin. [5][6][7][8] Although no deleterious mutation has been reported in TGFB3. 7,9 MSX1 has been suggested to function upstream of TGFB3 in the development of oral cleft.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have not been able to replicate this finding by either linkage or association [9,17,18]. Two meta-analyses, one looking at association studies [19] and a more recent study combining 13 genome scan studies [20•], reveal positive results, corroborating the hypothesis that TGFA is a modifier rather than necessary or sufficient to cause clefting.…”
Section: P13 (Tgfa)mentioning
confidence: 99%
“…However, there is no consensus among authors concerning the interaction between MSX1 and TGFA. Some studies show no statistically significant evidence of interaction between these genes in human tooth agenesis (Vieira et al 2004), whereas others indicate strong correlation (Jugessur et al 2003) among individuals with clefts.…”
Section: Interactions Among Other Genesmentioning
confidence: 97%